Environmental Impacts on the Strength Parameters of Mineral-Acrylic (PMMA/ATH) Facade Panels - Aleksander Byrdy; Michał Kołaczkowski (International Journal of Polymer Science)
Composite mineral-acrylic panels consist in 80% of natural minerals produced from bauxite (aluminium hydroxides (ATH)) and in 20% from acrylic resin (polymethyl methacrylate (PMMA)). This material due to high usability is widely used in interior finishes. Recently, the mineral-acrylic panels have been used as external claddings of buildings. So far, there are several dozen elevations realized worldwide. Due to the variability of the strength parameters of PMMA acrylic resins depending on the environmental influence, a number of tests on samples of mineral-acrylic panels to verify their suitability for use in climate conditions in Central Europe were performed. The studies determined the change of the material parameters after being subjected to aging process in conditions of high temperature, high relative humidity, freeze-thaw cycles, and UV radiation. In the studies parameters such as flexural strength and modulus of elasticity were measured at a reference temperature of 23°C. In raised and lowered temperatures only the tensile strength tests were conducted. Due to the lack of information in the available literature, the authors carried out tests of the temperature influence on the PMMA/ATH composite modulus of elasticity and flexural strength which is crucial in designing process.